Adhesive composition
By developing a two-component thermally conductive epoxy-acrylic hybrid adhesive, the problems of poor adhesion and slow curing speed of existing adhesives on nickel-plated steel are solved, and good adhesion and rapid curing to nickel-plated steel are achieved, which is suitable for the manufacturing of cylindrical battery cells.
Patent Information
- Application Number
- CN202380053084.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-14
- Filing Date
- 2023-06-02
- Publication Date
- 2025-02-28
AI Technical Summary
The existing adhesives have poor adhesion and slow curing speed when bonding nickel-plated steel, making it difficult to meet the rapid curing needs of cylindrical battery cells.
A two-component thermally conductive epoxy-acrylic hybrid adhesive is developed, including methacrylate monomer, elastomer toughener, phosphorus-containing compound and thermal filler. By mixing parts A and part B, the adhesive mixture is formed to ensure that the adhesive contains 40-90% by weight of the thermally conductive filler.
It achieves good adhesion to nickel-plated steel and quickly cures at room temperature, meeting the rapid curing needs of cylindrical battery cells, and improving the thermal conductivity of the adhesive.
Smart Images

Figure BDA0005236694440000041 
Figure BDA0005236694440000051 
Figure BDA0005236694440000071
Abstract
Description
Technical Field
[0001] The present invention relates to the field of epoxy-acrylic adhesive compositions. Background Art
[0002] When assembling an electric vehicle battery pack, there are many different design philosophies. However, most battery packs today are assembled in a modular fashion, where multiple battery pack subassemblies or modules are built and placed into a battery pack. Each module contains an array of battery cells that are thermally connected to some form of active liquid-cooled cooling unit (cooling channels, cold plates, etc.) via thermal interface materials (TIMs). The thermal connection between the battery cells and the cooling unit is critical to managing the heat generated during the charging and discharging of the battery cells, which allows the battery cells to have higher performance efficiency and life.
[0003] Three different types of battery cells are commonly used today: prismatic cells, pouch cells, and cylindrical cells. Prismatic cells and pouch cells typically have a polymer coating on the outside of the cell, which can facilitate bonding of the cell to a thermally conductive adhesive. Such coatings allow a wide range of chemistries to be used in bonding applications. However, cylindrical cells have a can (outer wall) that is typically constructed using nickel-plated steel. Nickel is notoriously difficult to bond for the following reasons: (1) nickel is an inherently inert material, meaning that its surface energy is lower than other metals, (2) nickel-plated surfaces have a lower surface roughness, and (3) known nickel plating processes provide surfaces with different properties. In addition, cylindrical cell designs may require adhesives with fast curing speeds to reduce cycle times. Cycle time becomes particularly important when designing a battery cell array that is bonded to both the top and bottom of a single cold plate, as the process will require the adhesive to have reached handling strength before the cold plate is flipped over.
[0004] Finally, cylindrical battery cells are the most commonly used because their manufacturing process may be simpler and potentially cheaper in the future. They are also commonly used in designs where engineers want to use the mechanical stiffness of the battery cell to impart stiffness to the vehicle structure. In this type of design, high-strength / high-modulus adhesives are ideal to help transfer the stiffness of the battery cell to the vehicle structure.
[0005] Polyurethanes, silicones, and epoxies can offer some of their own advantages in the assembly of cylindrical battery cell based designs when combined with thermally conductive filler packages. However, such adhesives are often slow to cure and / or have poor adhesion to nickel plated steel, especially when they contain the high filler loadings required to make them thermally conductive. Summary of the invention
[0006] In a first aspect, the present invention provides a two-component thermally conductive epoxy-acrylic hybrid adhesive comprising:
[0007] Part A
[0008] ai) at least one methacrylate monomer;
[0009] aii) at least one elastomeric toughening agent;
[0010] aiii) phosphorus-containing compounds including monoesters of phosphonic acid, monoesters and diesters of phosphonic acid and monoesters and diesters of phosphoric acid having one unit containing vinyl or allylic unsaturation;
[0011] aiv) tertiary amine free radical initiator;
[0012] av) 0.0025-0.065 wt % of diethylhydroxylamine;
[0013] Part B
[0014] bi) at least one epoxy resin;
[0015] bii) oxidizing agents;
[0016] Part A and / or part B comprises a thermally conductive filler, such that when part A and part B are mixed together to form an adhesive mixture, the adhesive mixture comprises 40-90 wt % of the thermally conductive filler.
[0017] In a second aspect, the present invention provides a method for bonding two or more substrates, the method comprising the steps of:
[0018] (1) A two-component thermally conductive epoxy-acrylic hybrid adhesive is provided, comprising:
[0019] Part A
[0020] ai) at least one methacrylate monomer;
[0021] aii) at least one elastomeric toughening agent;
[0022] aiii) phosphorus-containing compounds including monoesters of phosphonic acid, monoesters and diesters of phosphonic acid and monoesters and diesters of phosphoric acid having one unit containing vinyl or allylic unsaturation;
[0023] aiv) tertiary amine free radical initiator;
[0024] av) 0.0025-0.065 wt % of diethylhydroxylamine;
[0025] Part B
[0026] bi) at least one epoxy resin;
[0027] bii) oxidizing agents;
[0028] wherein part A and / or part B comprises a thermally conductive filler, such that when part A and part B are mixed together to form an adhesive mixture, the adhesive mixture comprises 40-90 wt % of the thermally conductive filler;
[0029] (2) mixing Part A and Part B to obtain an adhesive mixture;
[0030] (3) applying the adhesive mixture to the first substrate, the second substrate, or both;
[0031] (4) bringing the first substrate and the second substrate into bonding contact; and
[0032] (5) Curing the adhesive mixture. DETAILED DESCRIPTION
[0033] The inventors have discovered that an epoxy-acrylic adhesive having good adhesion to nickel plated steel, an open time greater than 16 minutes, and being storage stable can be achieved.
[0034] Definitions and Abbreviations
[0035] THFMA Tetrahydrofurfuryl methacrylate
[0036] CHMA Cyclohexyl Methacrylate
[0037] ATH Alumina Trihydrate
[0038] MAA Methacrylic acid
[0039] HEMA Hydroxyethyl Methacrylate Phosphate
[0040] SEC Size Exclusion Chromatography
[0041] RH Relative humidity
[0042] CF Cohesive Failure
[0043] AF Bond Failure
[0044] Equivalent weights and molecular weights are measured by gel permeation chromatography (GPC) using the method and instrumentation listed in the Examples section.
[0045] At least one methacrylate monomer (ai)
[0046] Part A of the adhesive comprises at least one methacrylate monomer. There is no particular limitation on the methacrylate monomer. Examples include monomers having the general structure I:
[0047]
[0048] Wherein R is an organic group.
[0049] In a preferred embodiment, R is selected from H, C1-C2 which may contain one or more heteroatoms. 18 A substituted or unsubstituted cyclic or non-cyclic aliphatic hydrocarbon group, and a C4-C 18 Aromatic hydrocarbon group.
[0050] More preferably, R is selected from C1-C 18 Substituted or unsubstituted cyclic or non-cyclic aliphatic hydrocarbon group, in particular, R is cyclohexyl or CH2-THF, wherein THF is 2- or 3-tetrahydrofurfuryl.
[0051] Other examples of methacrylate monomers include isobornyl methacrylate, cyclohexyl methacrylate, methyl methacrylate, and mixtures of these.
[0052] In some embodiments, part A comprises two or more methacrylate monomers.
[0053] In a preferred embodiment, part A comprises tetrahydrofurfuryl methacrylate (CAS [2455-24-5]).
[0054] In another preferred embodiment, part A comprises cyclohexyl methacrylate (CAS [101-43-9]).
[0055] In another preferred embodiment, part A comprises methacrylic acid.
[0056] In a particularly preferred embodiment, part A comprises tetrahydrofurfuryl methacrylate and cyclohexyl methacrylate.
[0057] In another particularly preferred embodiment, part A comprises tetrahydrofurfuryl methacrylate, cyclohexyl methacrylate and methacrylic acid.
[0058] In another preferred embodiment, part A comprises an adhesion promoter in the form of a divalent metal salt of methacrylic acid, in particular zinc dimethacrylate.
[0059] In another preferred embodiment, part A comprises a crosslinker. The crosslinker is a molecule having a molecular weight of 1,000 Da or less and two or more methacrylate groups. In a preferred embodiment, the crosslinker has a molecular weight of 900 Da or less.
[0060] In another preferred embodiment, the crosslinker has two methacrylate groups.
[0061] In another preferred embodiment, the cross-linking agent has a molecular weight of 900 Da or less and two methacrylate groups.
[0062] Examples of suitable crosslinking agents are molecules having the following general formula II:
[0063]
[0064] wherein x and y are independently selected from 2 to 10. In a preferred embodiment, x and y are both 5.
[0065] If used, the crosslinker is preferably present at 0.5-2.5 wt % based on the total weight of Part A, more preferably 0.6-1.25 wt %, particularly preferably 0.6-0.8 wt %.
[0066] In a preferred embodiment, the crosslinking agent has the general formula II and is present in an amount of 0.5-2.5 wt %, based on the total weight of part A, more preferably 0.6-1.25 wt %, particularly preferably 0.6-0.8 wt %.
[0067] In another particularly preferred embodiment, part A comprises tetrahydrofurfuryl methacrylate, cyclohexyl methacrylate, and a divalent metal salt of methacrylic acid, in particular zinc dimethacrylate.
[0068] Based on the total weight of part A, the one or more methacrylate monomers other than the adhesion promoter and the crosslinking agent preferably account for 10-30 wt % of part A, more preferably 12-25 wt %, particularly preferably 14-20 wt %.
[0069] In a preferred embodiment, part A comprises 0.3-8 wt %, more preferably 0.5-5 wt %, of tetrahydrofurfuryl methacrylate based on the total weight of part A.
[0070] In another preferred embodiment, part A comprises 5-20 wt %, more preferably 7-15 wt %, and very particularly preferably 10-13 wt %, of cyclohexyl methacrylate, based on the total weight of part A.
[0071] In another preferred embodiment, part A comprises 1-6 wt %, more preferably 2-4 wt %, of methacrylic acid based on the total weight of part A.
[0072] In another preferred embodiment, part A comprises 0.25-4 wt %, more preferably 0.5-1.5 wt %, of a divalent metal salt of methacrylic acid based on the total weight of part A.
[0073] In another preferred embodiment, part A comprises 0.5-4 wt %, more preferably 0.75-1.5 wt %, of zinc dimethacrylate based on the total weight of part A.
[0074] In another preferred embodiment, part A comprises 0.3-8 wt%, more preferably 0.5-5 wt%, of tetrahydrofurfuryl methacrylate, based on the total weight of part A, and 5-20 wt%, more preferably 7-15 wt%, more particularly preferably 10-13 wt%, of cyclohexyl methacrylate, based on the total weight of part A.
[0075] In another preferred embodiment, part A comprises 0.3-8 wt%, more preferably 0.5-5 wt%, of tetrahydrofurfuryl methacrylate, based on the total weight of part A, 5-20 wt%, more preferably 7-15 wt%, more particularly preferably 10-13 wt%, of cyclohexyl methacrylate, based on the total weight of part A, and 1-6 wt%, more preferably 2-4 wt%, of methacrylic acid, based on the total weight of part A.
[0076] In another preferred embodiment, part A comprises 0.3-8 wt%, more preferably 0.5-5 wt%, of tetrahydrofurfuryl methacrylate, based on the total weight of part A, 5-20 wt%, more preferably 7-15 wt%, more particularly preferably 10-13 wt%, of cyclohexyl methacrylate, based on the total weight of part A, 1-6 wt%, more preferably 2-4 wt%, of methacrylic acid, based on the total weight of part A, and 0.5-4 wt%, more preferably 0.75-1.5 wt%, of zinc dimethacrylate, based on the total weight of part A.
[0077] At least one toughening agent (aii)
[0078] Part A comprises at least one elastomeric toughening agent.
[0079] The toughening agent can be any elastomer compatible with the adhesive matrix. Such toughening agents are preferably selected from chlorinated or chlorosulfonated polyethylene, block copolymers of styrene and conjugated dienes (SBS, SIS), ethylene acrylic elastomers, core-shell graft copolymers, polyurethane-based toughening agents, polybutadiene, and butadiene-acrylonitrile-based toughening agents.
[0080] In a preferred embodiment, the at least one toughening agent is selected from acrylate or methacrylate functional polyurethanes, vinyl terminated polybutadienes, and vinyl terminated butadiene-acrylonitrile.
[0081] Polyurethane-based toughening agents
[0082] Polyurethane based tougheners are prepared by reacting a polyether polyol with a polyisocyanate in a ratio such that the resulting polymer is an NCO terminated polymer, followed by end-capping with methacrylic acid or a hydroxyalkyl ester of acrylic acid.
[0083] There is no particular limitation on the polyether polyol. The polyether polyol may be a diol or a triol, with a diol being preferred.
[0084] In a preferred embodiment, the polyol is a poly(C2-C6-alkylene oxide) glycol, with C2, C3 and C4 being preferred, and C4 being particularly preferred [ie poly(tetramethylene oxide) glycol or PTMEG].
[0085] In another preferred embodiment, the polyether polyol is selected from PTMEG having a molecular weight of 1,000 to 3,000 Da, more preferably 2,000 Da.
[0086] The toughening agent may also contain a low molecular weight (<250 Da) polyol having a functionality of 3 or 4, such as trimethylolpropane. If present, the low molecular weight polyol is preferably used at 0.1-3 wt%, more preferably 0.25-1 wt%, particularly preferably 0.5 wt%, based on the total weight of the toughening agent. In a preferred embodiment, the toughening agent contains 0.1-3 wt%, more preferably 0.25-1 wt%, particularly preferably 0.5 wt% of trimethylolpropane based on the total weight of the toughening agent.
[0087] There is no particular limitation on the polyisocyanate. The polyisocyanate may be aliphatic or aromatic, with aliphatic ones being preferred.
[0088] The polyisocyanate is preferably a diisocyanate.
[0089] In a preferred embodiment, the polyisocyanate is an aliphatic diisocyanate. Examples include hexamethylene diisocyanate (HDI), isophorone diisocyanate, methylene dicyclohexyl diisocyanate.
[0090] In a preferred embodiment, the polyether polyol is a diol and the polyisocyanate is a diisocyanate.
[0091] In another preferred embodiment, the polyether polyol is an aliphatic diol and the polyisocyanate is an aliphatic diisocyanate.
[0092] In another preferred embodiment, the polyether polyol is PTMEG and the polyisocyanate is HDI.
[0093] The hydroxyalkyl ester of methacrylic acid is preferably a C2-C6-hydroxyalkyl ester, more preferably a C2-C4-hydroxyalkyl ester, even more preferably a C2-C3-hydroxyalkyl ester, wherein C2-hydroxyalkyl ester is most preferred, in particular hydroxyethyl methacrylate (HEMA):
[0094]
[0095] The toughening agent is preferably made by reacting a polyether polyol with a polyisocyanate in the presence of a polyurethane catalyst to produce an NCO-terminated prepolymer. The prepolymer is then reacted with a hydroxyalkyl methacrylate to result in end-capping.
[0096] In a preferred embodiment, the toughening agent is made by reacting PTMEG with HDI in the presence of a polyurethane catalyst to produce an NCO-terminated prepolymer. The prepolymer is then reacted with HEMA, resulting in end-capping. The resulting toughening agent has the general formula III:
[0097]
[0098] wherein x has a value of 13 to 42, more preferably 27.8 (this corresponds to a PTMEG molecular weight of 1,000 to 3,000 Da, more preferably 2,000 Da), and y has a value of 1.5 to 5 or 1.8 to 4.9, more preferably 2.6.
[0099] In a preferred embodiment, the toughening agent has the general formula III, having a number average molecular weight (M) of 6,119 Da. n ), as determined by gel permeation chromatography (GPC) according to the method described in the Examples section.
[0100] In a preferred embodiment, the toughening agent has the general formula III, PTMEG has a molecular weight of 2,000 Da, and the toughening agent has a number average molecular weight (M n ), as determined by gel permeation chromatography (GPC) according to the method described in the Examples section.
[0101] In a preferred embodiment, the toughening agent has the general formula III, having a weight average molecular weight (M) of 15,084 Da. w ), as determined by gel permeation chromatography (GPC) according to the method described in the Examples section.
[0102] In a preferred embodiment, the toughening agent has the general formula III, PTMEG has a molecular weight of 2,000 Da, and the toughening agent has a weight average molecular weight (M w ), as determined by gel permeation chromatography (GPC) according to the method described in the Examples section.
[0103] Rubber-based tougheners
[0104] Suitable rubber-based toughening agents are those having a rubber core terminated with methacrylate or acrylate groups.
[0105] The rubber may be selected, for example, from silicone, polybutadiene, acrylonitrile-butadiene, polyacrylates or polymethacrylates, and mixtures of these.
[0106] Elastomer toughening agent content
[0107] In a preferred embodiment, part A comprises 5-20 wt %, more preferably 7-15 wt %, particularly preferably 8-12 wt %, of toughening agent (aii), based on the total weight of part A.
[0108] In another preferred embodiment, part A comprises 5-20 wt%, more preferably 7-15 wt%, particularly preferably 8-12 wt% of a toughener (aii), based on the total weight of part A, wherein the toughener is a rubber-based toughener terminated with methacrylate groups.
[0109] In another preferred embodiment, part A comprises 5-20 wt%, more preferably 7-15 wt%, particularly preferably 8-12 wt% of a toughener (aii), based on the total weight of part A, wherein the toughener is a rubber-based toughener terminated with methacrylate groups, wherein the rubber is selected from polyurethane, silicone, polybutadiene, acrylonitrile butadiene, polyacrylate or polymethacrylate, and mixtures of these.
[0110] In another preferred embodiment, part A contains 5-20 wt%, more preferably 7-15 wt%, particularly preferably 8-12 wt% of a toughening agent (aii), based on the total weight of part A, wherein the toughening agent is wherein the toughening agent is made by reacting an aliphatic polyether diol with an aliphatic diisocyanate.
[0111] In another preferred embodiment, part A comprises 5-20 wt%, more preferably 7-15 wt%, particularly preferably 8-12 wt% of a toughener (aii), based on the total weight of part A, wherein the toughener is made by reacting an aliphatic polyether diol with an aliphatic diisocyanate and subsequently capping with a C2-C6-hydroxyalkyl ester, more preferably a C2-C4-hydroxyalkyl ester, even more preferably a C2-C3-hydroxyalkyl ester of methacrylate, wherein C2-hydroxyalkyl is most preferred (hydroxyethyl methacrylate, HEMA).
[0112] In another preferred embodiment, part A comprises 5-20 wt%, more preferably 7-15 wt%, particularly preferably 8-12 wt% of a toughening agent (aii), based on the total weight of part A, wherein the toughening agent is produced by reacting PTMEG with HDI and subsequently capping with C2-C6-hydroxyalkyl esters, more preferably C2-C4-hydroxyalkyl esters, even more preferably C2-C3-hydroxyalkyl esters of methacrylate, wherein C2-hydroxyalkyl is most preferred (hydroxyethyl methacrylate, HEMA).
[0113] In another preferred embodiment, part A comprises 5-20 wt%, more preferably 7-15 wt%, particularly preferably 8-12 wt% of a toughening agent (aii), based on the total weight of part A, wherein the toughening agent is made by reacting PTMEG with HDI and subsequently capping with HEMA.
[0114] In another preferred embodiment, part A comprises 5-20 wt%, more preferably 7-15 wt%, particularly preferably 8-12 wt% of a toughening agent (aii), based on the total weight of part A, wherein the toughening agent has formula III:
[0115]
[0116] wherein x has a value of 13 to 42, more preferably 27.73 (this corresponds to a PTMEG molecular weight of 1,000 to 3,000 Da, more preferably 2,000 Da), and y has a value of 1.5 to 5 or 1.8 to 4.9, more preferably 2.6.
[0117] Phosphorus-containing compounds (aiii)
[0118] Part A comprises a phosphorus-containing compound selected from monoesters of phosphonic acid having one unit in which vinyl or allylic unsaturation is present, monoesters and diesters of phosphonic acid and monoesters, diesters and triesters of phosphoric acid.
[0119] Preferably, the phosphorus-containing compound (aiii) has the formula IV, V and VI:
[0120]
[0121] wherein W are the same or different and each W is independently selected from H and a divalent organic group, wherein at least one W is a divalent organic group, and at least one X is vinyl, and the other X is vinyl or absent (in the case where W is H), or H.
[0122] In another preferred embodiment, the phosphorus-containing compound (aiii) has Formula VI.
[0123] In another preferred embodiment, the phosphorus-containing compound (aiii) has formula VI, and one, two or three X groups are vinyl groups. Preferably, one X group is vinyl.
[0124] In another preferred embodiment, the phosphorus-containing compound (aiii) has formula VI, and one, two or three WX groups have formula VII:
[0125]
[0126] Wherein the dot represents the point of attachment of the group. In the case where one or two WX groups have formula VII, the remaining WX groups are preferably H. In a particularly preferred embodiment, one WX group has formula VI and the remaining WX groups are H, resulting in formula VIII:
[0127]
[0128] In another particularly preferred embodiment, two WX groups have formula VII, and the remaining WX groups are H, resulting in formula IX:
[0129]
[0130] In another preferred embodiment, the phosphorus-containing compound (aiii) is an approximately 2:1 mixture of Formula VIII and Formula IX.
[0131] Other examples of phosphorus-containing compounds include, but are not limited to, phosphoric acid; 2-methacryloyloxyethyl phosphate; bis-(2-methacryloyloxyethyl) phosphate; 2-acryloyloxyethyl phosphate; bis-(2-acryloyloxyethyl) phosphate; methyl-(2-methacryloyloxyethyl) phosphate; ethyl methacryloyloxyethyl phosphate; methacryloyloxyethyl phosphate; ethyl acryloyloxyethyl phosphate; propyl acryloyloxyethyl phosphate, isobutyl acryloyloxyethyl phosphate, ethylhexyl acryloyloxyethyl phosphate, halogenated propyl acryloyloxyethyl phosphate, halogenated isobutyl acryloyloxyethyl phosphate, or halogenated ethylhexyl acryloyloxyethyl phosphate. Phosphoric acid; vinylphosphonic acid; cyclohexene-3-phosphonic acid; (α-hydroxybutylene-2-phosphonic acid; 1-hydroxy-1-phenylmethane-1,1-diphosphonic acid; 1-hydroxy-1-methyl-1-diphosphonic acid; 1-amino-1phenyl-1,1-diphosphonic acid; 3-amino-3-hydroxypropane-1,1-diphosphonic acid; amino-tri(methylenephosphonic acid); γ-amino-propylphosphonic acid; γ-glycidyloxypropylphosphonic acid; phosphoric acid-mono-2-aminoethyl ester; allylphosphonic acid; allylphosphinic acid; β-methacryloyloxyethylphosphinic acid; diallylphosphinic acid; β-methacryloyloxyethyl)phosphinic acid and allylmethacryloyloxyethylphosphinic acid. Preferred phosphorus compounds are 2-hydroxyethyl methacrylate phosphate and phosphonated (meth)acrylic acid monomers.
[0132] Tertiary amine free radical initiator (AIV)
[0133] Part A contains a tertiary amine free radical initiator. There is no particular limitation on the tertiary amine free radical initiator.
[0134] Preferred tertiary amine free radical initiators have the general formula X:
[0135]
[0136] wherein W is selected from the group consisting of hydrogen, hydroxy, amino, halogen, alkyl having 1 to 8, preferably 1 to 4 carbon atoms, and alkoxy having 1 to 8, preferably 1 to 4 carbon atoms; R 1 and R 2 Independently selected from branched or straight chain C 1-4 -alkyl; and b is 1 or 2.
[0137] Examples include N,N-dimethylaniline, N,N-dimethylaminomethylphenol and N,N-dimethyl-p-toluidine.
[0138] In a particularly preferred embodiment, the tertiary amine free radical initiator is N,N-dimethyl-p-toluidine.
[0139] The tertiary amine free radical initiator is preferably used in an amount of 0.1-0.6 wt % based on the total weight of Part A, more preferably 0.2-0.4 wt %.
[0140] In a preferred embodiment, the tertiary amine free radical initiator is N,N-dimethyl-p-toluidine, which is used at 0.1-0.6 wt %, more preferably 0.2-0.4 wt %, based on the total weight of Part A.
[0141] Diethylhydroxylamine (av)
[0142] Part A contains 0.0025-0.065 wt% diethylhydroxylamine.
[0143] In a preferred embodiment, diethylhydroxylamine is present in part A at 0.015-0.06 wt %, more preferably 0.2-0.055 wt %, based on the total weight of part A.
[0144] At least one epoxy resin (bi)
[0145] Part B comprises at least one epoxy resin.
[0146] Suitable epoxy resins include diglycidyl ethers of polyphenolic compounds (such as resorcinol, catechol, hydroquinone, bisphenol, bisphenol A, bisphenol AP (1,1-bis(4-hydroxyphenyl)-1-phenylethane), bisphenol F, bisphenol K, bisphenol M, tetramethylbiphenol), diglycidyl ethers of aliphatic diols and polyether diols (such as C 2-24 diglycidyl ethers of bisphenol A resins, such as those marketed by Olin Corporation under the name PANOL. and Resin for sale.
[0147] In a preferred embodiment, the at least one epoxy resin comprises the reaction product of epichlorohydrin and bisphenol A.
[0148] In another preferred embodiment, the at least one epoxy resin comprises the liquid reaction product of epichlorohydrin and bisphenol A.
[0149] In a preferred embodiment, the at least one epoxy resin comprises an epoxy resin that is a liquid reaction product of epichlorohydrin and bisphenol A, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
[0150] In another preferred embodiment, the at least one epoxy resin comprises a bisphenol A / F based epoxy resin having an epoxy equivalent weight of 345-365 g / equivalent.
[0151] In a particularly preferred embodiment, the at least one epoxy resin comprises a mixture of a liquid reaction product of epichlorohydrin and bisphenol A and an epoxy resin based on bisphenol A / F having an epoxy equivalent weight of 345-365 g / equivalent, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
[0152] In a preferred embodiment, the at least one epoxy resin comprises 50-95 wt%, more preferably 60-80 wt%, based on the total weight of the epoxy resins in part B, of a liquid reaction product of epichlorohydrin and bisphenol A, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
[0153] In another preferred embodiment, the at least one epoxy resin comprises 5-50 wt%, more preferably 20-40 wt%, based on the total weight of the epoxy resins in Part B, of a bisphenol A / F based epoxy resin having an epoxy equivalent weight of 345-365 g / equivalent.
[0154] In another preferred embodiment, the at least one epoxy resin comprises 50-95 wt%, more preferably 60-80 wt%, of a liquid reaction product of epichlorohydrin and bisphenol A, based on the total weight of the epoxy resins in part B, and 5-50 wt%, more preferably 20-40 wt%, of an epoxy resin based on bisphenol A / F with an epoxy equivalent weight of 345-365 g / equivalent, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
[0155] Part B preferably comprises 10 to 30 wt %, more preferably 12 to 20 wt %, very particularly preferably 14 to 16 wt %, of at least one epoxy resin, based on the total weight of part B.
[0156] Oxidant (bii)
[0157] Part B contains an oxidizing agent. There is no particular limitation on the oxidizing agent.
[0158] Representative oxidants include, but are not limited to, organic peroxides such as benzoyl peroxide and other diacyl peroxides, hydroperoxides such as cumene hydroperoxide, peresters such as β-butyl peroxybenzoate; ketone hydroperoxides such as methyl ethyl ketone hydroperoxide, organic salts of transition metals such as cobalt naphthenate, and labile chlorine-containing compounds such as sulfonyl chloride. The most preferred oxidant is benzoyl peroxide.
[0159] The oxidizing agent, preferably an organic peroxide, is preferably present in part B at 1.5-5 wt %, based on the total weight of part B, more preferably 2-4 wt %.
[0160] In a preferred embodiment, part B comprises 1.5-5 wt %, more preferably 2-4 wt %, of benzoyl peroxide based on the total weight of part B.
[0161] Thermally conductive fillers
[0162] The adhesive of the present invention comprises a thermally conductive filler such that when Part A and Part B are mixed together to form an adhesive mixture, the adhesive mixture comprises 40-90 wt% of the thermally conductive filler.
[0163] In a preferred embodiment, the adhesive of the present invention comprises a thermally conductive filler such that when Part A and Part B are mixed together to form an adhesive mixture, the adhesive mixture comprises 40-70 wt% of the thermally conductive filler.
[0164] The thermally conductive filler preferably comprises, consists essentially of, or consists entirely of one or more thermally conductive fillers having a thermal conductivity of about 3 W / mK to about 80 W / mK.
[0165] Examples of suitable thermally conductive fillers include aluminum hydroxide, aluminum oxide, aluminum powder, zinc oxide, boron nitride, and mixtures of these. Particularly preferably, the filler is selected from aluminum hydroxide, aluminum oxide, and mixtures of these. Most particularly preferred is aluminum hydroxide.
[0166] The thermally conductive filler preferably has a sufficiently low Mohs hardness that it is generally non-abrasive. Preferably, the conductive filler has a Mohs hardness of about 7.0 or less, preferably about 5.0 or less, and more preferably about 4.0 or less. The conductive filler may have a Mohs hardness of about 0.5 or greater, about 1.5 or greater, or about 2.0 or greater. An example of a non-abrasive conductive filler is aluminum hydroxide (i.e., ATH) powder, which typically has a Mohs hardness of 2.5-3. Aluminum hydroxide powder has a thermal conductivity of 3 to 80 W / mK, typically about 10 W / mK.
[0167] The adhesive mixture formed by combining Part A and Part B contains sufficient thermally conductive filler such that the thermal conductivity of the adhesive mixture after curing is at least about 0.9 W / mK or greater, preferably about 1.0 W / mK or greater.
[0168] The thermal conductivity was measured according to ASTM 5470-12 on a thermal interface material tester from ZFW, Stuttgart, wherein the test was carried out in Spaltplus mode at a thickness of 1.8-1.2 mm; the thermal interface material described was considered to be type I (viscous liquid) as described in ASTM 5470-12, the upper contact was heated to about 40°C and the lower contact to about 10°C, resulting in a sample temperature of about 25°C.
[0169] In a preferred embodiment, the thermally conductive filler is ATH.
[0170] Particularly preferably, the thermally conductive filler is an ATH with a multimodal particle size distribution. The expression multimodal particle size distribution means that if the particle size is plotted on the x-axis with particle size and on the y-axis with volume %, at least two main peaks are observed. When essentially only two main peaks are observed, the expression bimodal is used.
[0171] Particularly preferably, the thermally conductive filler is ATH having a bimodal particle size distribution.
[0172] The particle size distribution of alumina trihydrate is typically measured using laser diffraction, using water containing sodium pyrophosphate as the suspending agent.
[0173] In a preferred embodiment, the alumina trihydrate has the following particle size distribution:
[0174] D 10 =0.5μm
[0175] D 50 =8μm
[0176] D 90 =80μm.
[0177] The thermally conductive filler is present in part A and / or part B such that when the two components are mixed (preferably in a volume ratio of 2:1 to 10:1, more preferably 4:1) to form an adhesive mixture, the concentration of the thermally conductive filler in the adhesive mixture is at least 40 wt % based on the total weight of the adhesive mixture. In a preferred embodiment, the concentration of the thermally conductive filler in the adhesive mixture is 55-65 wt % based on the total weight of the adhesive mixture.
[0178] The thermally conductive filler may be present in part A, part B, or both. Preferably, both part A and part B contain a thermally conductive filler.
[0179] In a preferred embodiment, the concentration of the thermally conductive filler in part A is 40-90 wt %, more preferably 55-62 wt %, and particularly preferably 44-57 wt %, based on the total weight of part A.
[0180] In a preferred embodiment, the concentration of the thermally conductive filler in part B is 55-90 wt %, based on the total weight of part B, more preferably 60-70 wt %, particularly preferably 44-57 wt %.
[0181] In a preferred embodiment, the concentration of the thermally conductive filler in part A is 40-65wt%, more preferably 55-62wt%, and particularly preferably 44-57wt%, based on the total weight of part A, and the concentration of the thermally conductive filler in part B is 55-90wt%, more preferably 60-70wt%, and particularly preferably 44-57wt%, based on the total weight of part B.
[0182] Optional Ingredients
[0183] The adhesive of the present invention may contain additional optional ingredients such as, for example:
[0184] Stabilizers / radical scavengers may be added to both Part A and Part B to extend the shelf life of the unmixed parts. Examples of stabilizers / radical scavengers include 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, butylated hydroxytoluene (BHT), methyl ether of hydroquinone, hydroquinone, benzoquinone, naphthoquinone, and nitrile oxide.
[0185] Fillers such as wollastonite, talc, fumed silica, calcium carbonate and glass.
[0186] Additional optional ingredients may include, for example, adhesion promoters, pigments, thixotropic agents, wetting agents, reactive diluents, antioxidants, inhibitors, and stabilizers.
[0187] Suitable adhesion promoters include mono- and polysiloxanes functionalized with functional groups that can react with epoxy or methacrylate components, and trialkoxysilanes having epoxy, amine or mercapto functionality.
[0188] Manufacturing method
[0189] The liquid components of Part A are typically mixed to homogeneity under vacuum or an inert atmosphere. The solid components are then added and the mixture is mixed to homogeneity. The tertiary amine free radical initiator is then added. Part A may be stored under vacuum or an inert atmosphere until use.
[0190] Part B is typically prepared by mixing the liquid ingredients (except the oxidant) under vacuum or an inert atmosphere until homogeneous. The solid ingredients are then mixed therein and after the mixture is homogeneous, the oxidant is added. Part B may be stored under vacuum or an inert atmosphere until use.
[0191] How to use
[0192] When used, the adhesive parts A and B are mixed until homogeneous and immediately applied to the substrate. The typical mixing ratio of A:B is 2:1 to 10:1, with 4:1 being particularly preferred.
[0193] Suitable substrates include, for example, electrogalvanized steel, hot dip galvanized steel, cold rolled steel, aluminum, nickel plated steel, polymers and polymer composites.
[0194] Effects of the Invention
[0195] The adhesive of the present invention preferably shows a lap shear strength of 10 MPa or more on cold rolled steel using the following test method: Samples are prepared and tested according to SAE J1523 [2012 02 01]. 25.4 mm x 101.6 mm samples are mated at 12.7 mm overlap and 0.10 mm bond line thickness, and then allowed to cure at room temperature. Samples are tested at a rate of 12.7 mm / min.
[0196] The adhesive of the present invention preferably shows a lap shear strength of 10 MPa or more on nickel-plated steel using the following test method: Samples are prepared and tested according to SAE J1523 [2012 02 01]. 25.4 mm x 101.6 mm samples are mated at 12.7 mm overlap and 0.10 mm bond line thickness, and then allowed to cure at room temperature. Samples are tested at a rate of 12.7 mm / min.
[0197] When tested for lap shear strength as described above, the adhesives of the present invention preferably show a failure mode of at least 90%, more preferably at least 95% cohesive failure on cold rolled steel.
[0198] When tested for lap shear strength as described above, the adhesive of the present invention preferably exhibits a failure mode of at least 50%, more preferably at least 80% cohesive failure on nickel plated steel.
[0199] The adhesive of the present invention showed good storage stability as evidenced by the lack of gelation of Part A after heat aging at 54°C for two weeks.
[0200] Particularly preferred embodiments
[0201] The following are particularly preferred embodiments of the present invention:
[0202] 1. A two-component thermally conductive epoxy-acrylic hybrid adhesive comprising:
[0203] Part A
[0204] ai) at least one methacrylate monomer;
[0205] aii) at least one elastomeric toughening agent;
[0206] aiii) phosphorus-containing compounds including monoesters of phosphonic acid, monoesters and diesters of phosphonic acid and monoesters and diesters of phosphoric acid having one unit containing vinyl or allylic unsaturation;
[0207] aiv) tertiary amine free radical initiator;
[0208] av) 0.0025-0.065 wt % of diethylhydroxylamine;
[0209] Part B
[0210] bi) at least one epoxy resin;
[0211] bii) oxidizing agents;
[0212] Part A and / or part B comprises a thermally conductive filler, such that when part A and part B are mixed together to form an adhesive mixture, the adhesive mixture comprises 40-90 wt % of the thermally conductive filler.
[0213] 2. A method for bonding two or more substrates, the method comprising the steps of:
[0214] (1) A two-component thermally conductive epoxy-acrylic hybrid adhesive is provided, comprising:
[0215] Part A
[0216] ai) at least one methacrylate monomer;
[0217] aii) at least one elastomeric toughening agent;
[0218] aiii) phosphorus-containing compounds including monoesters of phosphonic acid, monoesters and diesters of phosphonic acid and monoesters and diesters of phosphoric acid having one unit containing vinyl or allylic unsaturation;
[0219] aiv) tertiary amine free radical initiator;
[0220] av) 0.0025-0.065 wt % of diethylhydroxylamine;
[0221] Part B
[0222] bi) at least one epoxy resin;
[0223] bii) oxidizing agents;
[0224] wherein part A and / or part B comprises a thermally conductive filler, such that when part A and part B are mixed together to form an adhesive mixture, the adhesive mixture comprises 40-90 wt % of the thermally conductive filler;
[0225] (2) mixing Part A and Part B to obtain an adhesive mixture;
[0226] (3) applying the adhesive mixture to the first substrate, the second substrate, or both;
[0227] (4) bringing the first substrate and the second substrate into bonding contact; and
[0228] (5) Curing the adhesive mixture.
[0229] 3. As described in embodiment 1 or 2, wherein the at least one methacrylate monomer has the general formula I:
[0230]
[0231] Wherein R is an organic group.
[0232] 4. As described in Example 3, wherein R is selected from H, C1-C2 which may contain one or more heteroatoms 18A substituted or unsubstituted cyclic or non-cyclic aliphatic hydrocarbon group, and a C4-C 18 Aromatic hydrocarbon group.
[0233] 5. As described in Example 3, wherein R is selected from C1-C 18 Substituted or unsubstituted cyclic or non-cyclic aliphatic hydrocarbon group, in particular, R is cyclohexyl or CH2-THF, wherein THF is 2- or 3-tetrahydrofurfuryl.
[0234] 6. As described in any preceding embodiment, wherein the at least one methacrylate monomer is selected from isobornyl methacrylate, cyclohexyl methacrylate, methyl methacrylate, and mixtures thereof.
[0235] 7. As described in any preceding embodiment, wherein part A comprises two or more methacrylate monomers.
[0236] 8. As described in any preceding embodiment, wherein moiety A comprises tetrahydrofurfuryl methacrylate (CAS [2455-24-5]).
[0237] 9. As described in any preceding embodiment, wherein part A comprises cyclohexyl methacrylate (CAS [101-43-9].
[0238] 10. As described in any preceding embodiment, wherein moiety A comprises methacrylic acid.
[0239] 11. As described in any preceding embodiment, wherein part A comprises tetrahydrofurfuryl methacrylate and cyclohexyl methacrylate.
[0240] 12. As described in any preceding embodiment, wherein part A comprises tetrahydrofurfuryl methacrylate, cyclohexyl methacrylate, and methacrylic acid.
[0241] 13. As described in any preceding embodiment, wherein part A comprises an adhesion promoter in the form of a divalent metal salt of methacrylic acid, particularly zinc dimethacrylate.
[0242] 14. As described in any preceding embodiment, wherein part A comprises a cross-linking agent.
[0243] 15. As described in embodiment 14, wherein the cross-linking agent is a molecule having a molecular weight of 1,000 Da or less and two or more methacrylate groups.
[0244] 16. As described in embodiment 14 or 15, wherein the cross-linking agent has a molecular weight of 900 Da or less.
[0245] 17. As described in embodiment 14, 15 or 16, wherein the crosslinker has two methacrylate groups.
[0246] 18. As described in embodiment 14, wherein the cross-linking agent has a molecular weight of 900 Da or less and two methacrylate groups.
[0247] 19. As described in any of the preceding embodiments, wherein part A comprises a cross-linking agent having the following general formula II:
[0248]
[0249] wherein x and y are independently selected from 2-10, preferably, x and y are both 10.
[0250] 20. As described in any preceding embodiment, wherein part A comprises 0.5-2.5 wt %, more preferably 0.6-1.25 wt %, and particularly preferably 0.6-0.8 wt % of the crosslinking agent based on the total weight of part A.
[0251] 21. As described in any of the preceding embodiments, wherein part A comprises a crosslinker having the general formula II and present in 0.5-2.5 wt %, more preferably 0.6-1.25 wt %, and particularly preferably 0.6-0.8 wt %, based on the total weight of part A.
[0252] 22. As described in any preceding embodiment, wherein part A comprises tetrahydrofurfuryl methacrylate, cyclohexyl methacrylate, and a divalent metal salt of methacrylic acid, particularly zinc dimethacrylate.
[0253] 23. As described in any of the preceding embodiments, based on the total weight of part A, the one or more methacrylate monomers other than the adhesion promoter and the crosslinking agent account for 10-30 wt %, more preferably 12-25 wt %, and particularly preferably 14-20 wt % of part A.
[0254] 24. As described in any preceding embodiment, wherein part A comprises 0.3-8 wt%, more preferably 0.5-5 wt%, of tetrahydrofurfuryl methacrylate based on the total weight of part A.
[0255] 25. As described in any preceding embodiment, wherein part A comprises 5-20 wt%, more preferably 7-15 wt%, and even more preferably 10-13 wt%, of cyclohexyl methacrylate based on the total weight of part A.
[0256] 26. As described in any preceding embodiment, wherein part A comprises 1-6 wt %, more preferably 2-4 wt % methacrylic acid based on the total weight of part A.
[0257] 27. As described in any preceding embodiment, wherein part A comprises 0.25-4 wt %, more preferably 0.5-1.5 wt %, of the divalent metal salt of methacrylic acid based on the total weight of part A.
[0258] 28. As described in any preceding embodiment, wherein part A comprises 0.5-4 wt %, more preferably 0.75-1.5 wt %, of zinc dimethacrylate based on the total weight of part A.
[0259] 29. As described in any of the preceding embodiments, part A comprises 0.3-8 wt%, more preferably 0.5-5 wt%, of tetrahydrofurfuryl methacrylate based on the total weight of part A, and 5-20 wt%, more preferably 7-15 wt%, and more particularly preferably 10-13 wt%, of cyclohexyl methacrylate based on the total weight of part A.
[0260] 30. As described in any of the preceding embodiments, part A comprises 0.3-8 wt%, more preferably 0.5-5 wt%, of tetrahydrofurfuryl methacrylate, based on the total weight of part A, 5-20 wt%, more preferably 7-15 wt%, more particularly preferably 10-13 wt%, of cyclohexyl methacrylate, based on the total weight of part A, and 1-6 wt%, more preferably 2-4 wt%, of methacrylic acid, based on the total weight of part A.
[0261] 31. As described in any of the preceding embodiments, part A comprises 0.3-8 wt%, more preferably 0.5-5 wt%, of tetrahydrofurfuryl methacrylate, based on the total weight of part A, 5-20 wt%, more preferably 7-15 wt%, more particularly preferably 10-13 wt%, of cyclohexyl methacrylate, based on the total weight of part A, 1-6 wt%, more preferably 2-4 wt%, of methacrylic acid, based on the total weight of part A, and 0.5-4 wt%, more preferably 0.75-1.5 wt%, of zinc dimethacrylate, based on the total weight of part A.
[0262] 32. As described in any of the preceding embodiments, the toughening agent is selected from chlorinated or chlorosulfonated polyethylene, block copolymers of styrene and conjugated dienes (SBS, SIS), ethylene acrylic elastomers, core-shell graft copolymers, polyurethane-based toughening agents, polybutadiene, and butadiene-acrylonitrile-based toughening agents.
[0263] 33. As described in any preceding embodiment, the toughening agent is selected from acrylate or methacrylate functional polyurethanes, vinyl terminated polybutadiene, and vinyl terminated butadiene-acrylonitrile.
[0264] 34. As described in any preceding embodiment, the toughening agent is selected from polyurethane-based toughening agents and rubber-based toughening agents.
[0265] 35. As described in any preceding embodiment, the toughening agent is a polyurethane based toughening agent prepared by reacting a polyether polyol with a polyisocyanate in a ratio such that the resulting polymer is an NCO terminated polymer, followed by end-capping with a hydroxyalkyl ester of methacrylic acid or acrylic acid.
[0266] 36. As described in any preceding embodiment, the toughening agent is a rubber based toughening agent, wherein the rubber is selected from silicone, polybutadiene, acrylonitrile butadiene, polyacrylate or polymethacrylate, and mixtures of these, terminated with vinyl, methacrylate or acrylate groups.
[0267] 37. As described in any of the preceding embodiments, part A comprises 5-20 wt%, more preferably 7-15 wt%, and particularly preferably 8-12 wt% of the toughening agent (aii), based on the total weight of part A.
[0268] 38. As described in any of the preceding embodiments, part A comprises 5-20 wt%, more preferably 7-15 wt%, and particularly preferably 8-12 wt% of a toughener (aii), based on the total weight of part A, wherein the toughener is a rubber-based toughener terminated with a methacrylate group.
[0269] 39. As described in any of the preceding embodiments, part A comprises 5-20 wt%, more preferably 7-15 wt%, and particularly preferably 8-12 wt% of a toughener (aii), based on the total weight of part A, wherein the toughener is a rubber-based toughener terminated with methacrylate groups, wherein the rubber is selected from polyurethane, silicone, polybutadiene, acrylonitrile butadiene, polyacrylate or polymethacrylate, and mixtures of these.
[0270] 40. As described in any of the preceding embodiments, part A comprises 5-20 wt%, more preferably 7-15 wt%, and particularly preferably 8-12 wt% of a toughener (aii), based on the total weight of part A, wherein the toughener is wherein the toughener is made by reacting an aliphatic polyether diol with an aliphatic diisocyanate, followed by end-capping with a C2-C6-hydroxyalkyl ester, more preferably a C2-C4-hydroxyalkyl ester, and even more preferably a C2-C3-hydroxyalkyl ester of methacrylate, wherein C2-hydroxyalkyl is most preferred (hydroxyethyl methacrylate, HEMA).
[0271] 41. As described in any of the preceding embodiments, wherein the phosphorus-containing compound (aiii) has Formula IV, V and VI:
[0272]
[0273] wherein W are the same or different and each W is independently selected from H and a divalent organic group, wherein at least one W is a divalent organic group, and at least one X is vinyl, and the other X is vinyl or absent (in the case where W is H), or H.
[0274] 42. As described in any preceding embodiment, wherein the phosphorus-containing compound (aiii) has Formula VI.
[0275] 43. As described in any of the preceding embodiments, wherein the phosphorus-containing compound (aiii) has formula VI, and one, two or three X groups are vinyl groups. Preferably, one X group is vinyl.
[0276] 44. As described in any of the preceding embodiments, wherein the phosphorus-containing compound (aiii) has formula VI, and one, two or three WX groups have formula VII:
[0277]
[0278] The dot represents the point of attachment of the group, and in the case where one or two WX groups are of formula VII, the remaining WX groups are preferably H.
[0279] 45. As described in any of the preceding embodiments, wherein the phosphorus-containing compound (aiii) has Formula VIII:
[0280]
[0281] 46. As described in any of the preceding embodiments, wherein the phosphorus-containing compound (aiii) has Formula IX:
[0282]
[0283] 47. As described in any preceding embodiment, wherein the phosphorus-containing compound (aiii) is about a 2:1 mixture of Formula VIII and Formula IX.
[0284] 48. As described in any of the preceding embodiments, the phosphorus-containing compound is selected from phosphoric acid; 2-methacryloyloxyethyl phosphate; bis-(2-methacryloyloxyethyl) phosphate; 2-acryloyloxyethyl phosphate; bis-(2-acryloyloxyethyl) phosphate; methyl-(2-methacryloyloxyethyl) phosphate; ethyl methacryloyloxyethyl phosphate; methacryloyloxyethyl phosphate; ethyl acryloyloxyethyl phosphate; propyl acryloyloxyethyl phosphate, isobutyl acryloyloxyethyl phosphate, ethylhexyl acryloyloxyethyl phosphate, halogenated propyl acryloyloxyethyl phosphate, halogenated isobutyl acryloyloxyethyl phosphate or halogenated ethylhexyl acryloyl Oxyethyl phosphate; vinylphosphonic acid; cyclohexene-3-phosphonic acid; (α-hydroxybutylene-2-phosphonic acid; 1-hydroxy-1-phenylmethane-1,1-diphosphonic acid; 1-hydroxy-1-methyl-1-diphosphonic acid; 1-amino-1phenyl-1,1-diphosphonic acid; 3-amino-3-hydroxypropane-1,1-diphosphonic acid; amino-tri(methylenephosphonic acid); γ-amino-propylphosphonic acid; γ-glycidyloxypropylphosphonic acid; mono-2-aminoethyl phosphate; allylphosphonic acid; allylphosphinic acid; β-methacryloyloxyethylphosphinic acid; diallylphosphinic acid; β-methacryloyloxyethyl)phosphinic acid and allylmethacryloyloxyethylphosphinic acid.
[0285] 49. As described in any of the preceding embodiments, wherein the tertiary amine free radical initiator (aiv) has the general formula X:
[0286]
[0287] wherein W is selected from the group consisting of hydrogen, hydroxy, amino, halogen, alkyl having 1 to 8, preferably 1 to 4 carbon atoms, and alkoxy having 1 to 8, preferably 1 to 4 carbon atoms; R 1 and R 2 Independently selected from branched or straight chain C 1-4 -alkyl; and b is 1 or 2.
[0288] 50. As described in any preceding embodiment, the tertiary amine free radical initiator is selected from N,N-dimethylaniline, N,N-dimethylaminomethylphenol and N,N-dimethyl-p-toluidine.
[0289] 51. As described in any preceding embodiment, wherein the tertiary amine free radical initiator is N,N-dimethyl-p-toluidine.
[0290] 52. As described in any of the preceding embodiments, wherein the tertiary amine free radical initiator is used in an amount of 0.1-0.6 wt %, more preferably 0.2-0.4 wt %, based on the total weight of Part A.
[0291] 53. As described in any preceding embodiment, wherein the tertiary amine free radical initiator is N,N-dimethyl-p-toluidine, used at 0.1-0.6 wt %, more preferably 0.2-0.4 wt %, based on the total weight of part A.
[0292] 54. As described in any preceding embodiment, wherein diethylhydroxylamine is present in part A at 0.015-0.06 wt %, more preferably 0.2-0.055 wt %, based on the total weight of part A.
[0293] 55. As described in any preceding embodiment, the at least one epoxy resin comprises the reaction product of epichlorohydrin and bisphenol A.
[0294] 56. As described in any preceding embodiment, wherein the at least one epoxy resin comprises an epoxy resin that is a liquid reaction product of epichlorohydrin and bisphenol A, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
[0295] 57. As described in any preceding embodiment, the at least one epoxy resin comprises a bisphenol A / F based epoxy resin having an epoxy equivalent weight of 345-365 g / equivalent.
[0296] 58. As described in any preceding embodiment, the at least one epoxy resin comprises a mixture of a liquid reaction product of epichlorohydrin and bisphenol A and a bisphenol A / F-based epoxy resin having an epoxy equivalent weight of 345-365 g / equivalent, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
[0297] 59. As described in any preceding embodiment, the at least one epoxy resin comprises 50-95 wt%, more preferably 60-80 wt%, based on the total weight of the epoxy resins in part B, of a liquid reaction product of epichlorohydrin and bisphenol A, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
[0298] 60. As described in any preceding embodiment, the at least one epoxy resin comprises 5-50 wt%, more preferably 20-40 wt%, of a bisphenol A / F based epoxy resin with an epoxy equivalent weight of 345-365 g / equivalent based on the total weight of the epoxy resins in Part B.
[0299] 61. As described in any preceding embodiment, the at least one epoxy resin comprises 50-95 wt%, more preferably 60-80 wt%, of a liquid reaction product of epichlorohydrin and bisphenol A, based on the total weight of the epoxy resins in part B, and 5-50 wt%, more preferably 20-40 wt%, of an epoxy resin based on bisphenol A / F with an epoxy equivalent weight of 345-365 g / equivalent, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
[0300] 62. As described in any preceding embodiment, part B comprises 10 to 30 wt %, more preferably 12 to 20 wt %, and more particularly preferably 14 to 16 wt % of the at least one epoxy resin, based on the total weight of part B.
[0301] 63. As described in any preceding embodiment, wherein the oxidizing agent (bi) is selected from organic peroxides.
[0302] 64. As described in any preceding embodiment, the oxidizing agent (bi) is selected from diacyl peroxides, hydroperoxides, peresters, and ketone hydroperoxides.
[0303] 65. As described in any preceding embodiment, wherein the oxidizing agent (bi) is selected from benzoyl peroxide, cumene hydroperoxide, beta-butyl peroxybenzoate, and methyl ethyl ketone hydroperoxide.
[0304] 66. As described in any preceding embodiment, wherein the oxidizing agent (bi) is benzoyl peroxide.
[0305] 67. As described in any preceding embodiment, wherein the oxidizing agent (bi) is present in part B at 1.5-5 wt%, more preferably 2-4 wt%, based on the total weight of part B.
[0306] 68. As described in any preceding embodiment, wherein part B comprises 1.5-5 wt%, more preferably 2-4 wt%, of benzoyl peroxide based on the total weight of part B.
[0307] 69. As described in any preceding embodiment, the thermally conductive filler comprises, consists essentially of, or consists entirely of one or more thermally conductive fillers having a thermal conductivity of about 3 W / mK to about 80 W / mK.
[0308] 70. As described in any of the preceding embodiments, the thermally conductive filler is selected from aluminum hydroxide, aluminum oxide, aluminum powder, zinc oxide, boron nitride, and mixtures thereof.
[0309] 71. As described in any preceding embodiment, wherein the thermally conductive filler is aluminum hydroxide.
[0310] 72. As described in any of the preceding embodiments, the adhesive mixture formed by mixing Part A and Part B contains sufficient thermally conductive filler so that the thermal conductivity of the adhesive mixture after curing is at least about 0.9 W / mK or greater, preferably about 1.0 W / mK or greater.
[0311] 73. As described in any preceding embodiment, wherein the thermally conductive filler is ATH having a multimodal particle size distribution.
[0312] 74. As described in any preceding embodiment, wherein the thermally conductive filler is ATH having a bimodal particle size distribution.
[0313] 75. As described in any preceding embodiment, the thermally conductive filler is alumina trihydrate having the following particle size distribution:
[0314] D 10 =0.5μm
[0315] D 50 =8μm
[0316] D 90 =80μm.
[0317] 76. As described in any of the preceding embodiments, the thermally conductive filler is present in part A and / or part B such that when the two components are mixed (preferably in a volume ratio of 2:1 to 10:1, more preferably 4:1) to form an adhesive mixture, the concentration of the thermally conductive filler in the adhesive mixture is at least 40 wt% based on the total weight of the adhesive mixture.
[0318] 77. As described in any of the preceding embodiments, the thermally conductive filler is present in part A and / or part B such that when the two components are mixed (preferably in a volume ratio of 2:1 to 10:1, more preferably 4:1) to form an adhesive mixture, the concentration of the thermally conductive filler in the adhesive mixture is 55-65 wt% based on the total weight of the adhesive mixture.
[0319] 78. As described in any preceding embodiment, the thermally conductive filler is present in part A, part B, or both.
[0320] 79. As described in any preceding embodiment, wherein both part A and part B contain thermally conductive fillers.
[0321] 80. As described in any preceding embodiment, the concentration of the thermally conductive filler in part A is 40-90 wt %, more preferably 55-62 wt %, and particularly preferably 44-57 wt %, based on the total weight of part A.
[0322] 81. As described in any preceding embodiment, the concentration of the thermally conductive filler in part B is 55-90 wt %, more preferably 60-70 wt %, and particularly preferably 44-57 wt %, based on the total weight of part B.
[0323] 82. As described in any of the preceding embodiments, the concentration of the thermally conductive filler in part A is 40-65wt%, more preferably 55-62wt%, and particularly preferably 44-57wt%, based on the total weight of part A, and the concentration of the thermally conductive filler in part B is 55-90wt%, more preferably 60-70wt%, and particularly preferably 44-57wt%, based on the total weight of part B.
[0324] 83. As described in any preceding embodiment, wherein the adhesive of the present invention shows a lap shear strength of 10 MPa or greater on cold rolled steel using the following test method: samples are prepared and tested according to SAE J1523 [2012 02 01], 25.4 mm x 101.6 mm samples are mated at 12.7 mm overlap and 0.10 mm bond line thickness, and then cured at room temperature, and the samples are tested at a rate of 12.7 mm / min.
[0325] 84. As described in any preceding embodiment, wherein the adhesive of the present invention shows a lap shear strength of 10 MPa or greater on nickel-plated steel using the following test method: specimens are prepared and tested according to SAE J1523 [2012 02 01], 25.4 mm x 101.6 mm specimens are mated at 12.7 mm overlap and 0.10 mm bond line thickness, and then cured at room temperature, and the specimens are tested at a rate of 12.7 mm / min.
[0326] 85. Any preceding embodiment, wherein the adhesive of the present invention exhibits a failure mode of at least 90%, more preferably at least 95%, cohesive failure on cold rolled steel when tested for lap shear strength as described above.
[0327] 86. Any preceding embodiment, wherein the adhesive of the present invention exhibits a failure mode of at least 50%, more preferably at least 80% cohesive failure on nickel plated steel when tested for lap shear strength as described above.
[0328] 87. As described in any preceding embodiment, wherein the adhesive of the present invention exhibits good storage stability as evidenced by the lack of gelation of Part A after heat aging at 54°C for two weeks.
[0329] Examples
[0330] The ingredients are listed in Table 1.
[0331]
[0332]
[0333]
[0334]
[0335] Preparation of adhesive
[0336] Using Hauschild Engineering's double asymmetric centrifugal FlackTek DAC400FVZ All formulations were mixed using the following procedure.
[0337] The ingredients listed in Table 2 were used to prepare the inventive and comparative samples.
[0338] Part A Procedure
[0339] The following procedure is performed under vacuum. Acrylic monomers (THFMA, CHMA) are added to a mixer along with zinc dimethacrylate, MAA, HEMA, Hypro (toughener), Dynasylan, SR480, Ethanox and DEHA, and the mixture is rapidly mixed at 2,300rpm for two minutes. ATH, talc, glass beads and fumed silica are added, and the mixture is rapidly mixed at 2,300rpm for two minutes. The container walls are scraped down, and the mixture is rapidly mixed at 2,300rpm for another two minutes. N,N-dimethyl-p-toluidine is added, and rapid mixing is continued at 2,100rpm for another minute. The sides of the container are scraped down, and mixing is continued at 2,100rpm for another minute. Part A is stored in a barrel under vacuum until use. The material is packaged at about 40°C to minimize entrained air.
[0340] Part B Procedure
[0341] Add epoxy resin and BHT to a speed mixer. Heat the mixture to 80°C for one hour to dissolve the BHT. Add all other liquids except Luperox (benzoyl peroxide) and speed mix the mixture at 2,100 rpm for two minutes. Add solid ingredients and speed mix the mixture at 2,100 rpm for two minutes. Scrape down the sides of the container and continue mixing at 2,100 rpm for two minutes. Cool the mixture to 40°C-50°C, add Luperox, and speed mix the mixture at 1,200 rpm for thirty seconds, followed by speed mixing at 2,100 rpm for two minutes. Store Part B in a cartridge under vacuum until use. Package with this material at about 40°C to minimize entrapped air.
[0342] Adhesive Dispensing and Application
[0343] Part A and Part B were dispensed at room temperature using an air powered spray gun through a 16 element static mixer. Prior to application of the adhesive, two beads of adhesive were blown through the mixer along the length of the mixer.
[0344] Open time
[0345] The two components were mixed by a static mixer at a volume ratio of 4:1. Immediately after dispensing a bead approximately 8 cm long 8 mm wide by 5 mm high, a timer was started and the time from dispensing the adhesive until the center of the bead solidified into a solid / gel was recorded - as determined by poking with a disposable popsicle stick. The results are listed in Table 2.
[0346] Lap shear strength
[0347] Lap shear data were collected on cold rolled steel (CRS) or plasma treated nickel plated steel (NPS). Samples were prepared and tested according to SAE J1523 [2012 02 01]. 25.4 mm x 101.6 mm samples were mated at 12.7 mm overlap and 0.10 mm bond line thickness and then cured at room temperature. Samples were tested at a rate of 12.7 mm / min. Results are listed in Table 2.
[0348] Part A Aging Test
[0349] To test the storage stability of Part A, the mixture was heated in an oven maintained at 54°C and the time to gel was recorded. The results are listed in Table 2.
[0350] Thermal conductivity
[0351] Thermal conductivity was measured according to ASTM D5470. A TIMTester from Linseis TIM was used for the test and was performed according to ASTM D5470. The measurement was performed using the Type III method, where a stack of 1.0 mm samples was used and silicone oil was used on the surface of each sample to reduce the contact resistance in the measurement. The bulk thermal conductivity λ (W / mK) was recorded. The results are listed in Table 2.
[0352]
[0353]
Claims
1. A two-component thermally conductive epoxy-acrylic hybrid adhesive comprising: Part A ai) at least one methacrylate monomer; aii) at least one elastomeric toughening agent terminated with methacrylate groups; aiii) phosphorus-containing compounds including monoesters of phosphonic acid, monoesters and diesters of phosphonic acid and monoesters and diesters of phosphoric acid having one unit containing vinyl or allylic unsaturation; aiv) tertiary amine free radical initiator; av) 0.0025-0.065 wt % of diethylhydroxylamine; Part B bi) at least one epoxy resin; bii) oxidizing agents; Part A and / or part B comprises a thermally conductive filler, such that when part A and part B are mixed together to form an adhesive mixture, the adhesive mixture comprises 40-90 wt % of the thermally conductive filler.
2. A method for bonding two or more substrates, the method comprising the steps of: (1) A two-component thermally conductive epoxy-acrylic hybrid adhesive is provided, comprising: Part A ai) at least one methacrylate monomer; aii) at least one elastomeric toughening agent terminated with methacrylate groups; aiii) phosphorus-containing compounds including monoesters of phosphonic acid, monoesters and diesters of phosphonic acid and monoesters and diesters of phosphoric acid having one unit containing vinyl or allylic unsaturation; aiv) tertiary amine free radical initiator; av) 0.0025-0.065 wt % of diethylhydroxylamine; Part B bi) at least one epoxy resin; bii) oxidizing agents; wherein part A and / or part B comprises a thermally conductive filler, such that when part A and part B are mixed together to form an adhesive mixture, the adhesive mixture comprises 40-90 wt % of the thermally conductive filler; (2) mixing Part A and Part B to obtain an adhesive mixture; (3) applying the adhesive mixture to the first substrate, the second substrate, or both; (4) bonding the first substrate and the second substrate into contact with each other; as well as (5) Curing the adhesive mixture.
3. As claimed in claim 1 or 2, wherein: The at least one methacrylate monomer has the general formula I: Wherein R is an organic group.
4. As claimed in claim 3, wherein R is selected from H, C1-C2 which may contain one or more heteroatoms 18 A substituted or unsubstituted cyclic or non-cyclic aliphatic hydrocarbon group, and a C4-C 18 Aromatic hydrocarbon group.
5. As claimed in claim 3, wherein R is selected from C1-C 18 Substituted or unsubstituted cyclic or non-cyclic aliphatic hydrocarbon group, in particular, R is cyclohexyl or CH2-THF, wherein THF is 2- or 3-tetrahydrofurfuryl.
6. A method as claimed in any preceding claim, wherein: The at least one methacrylate monomer is selected from the group consisting of isobornyl methacrylate, cyclohexyl methacrylate, methyl methacrylate, and mixtures of these.
7. A method as claimed in any preceding claim, wherein: Part A comprises two or more methacrylate monomers.
8. A method as claimed in any preceding claim, wherein: Part A contains tetrahydrofurfuryl methacrylate (CAS [2455-24-5]).
9. A method as claimed in any preceding claim, wherein: Part A contains cyclohexyl methacrylate (CAS [101-43-9].
10. A method as claimed in any preceding claim, wherein: Part A comprises methacrylic acid.
11. A method as claimed in any preceding claim, wherein: Part A comprises tetrahydrofurfuryl methacrylate and cyclohexyl methacrylate.
12. A method as claimed in any preceding claim, wherein: Part A comprises tetrahydrofurfuryl methacrylate, cyclohexyl methacrylate and methacrylic acid.
13. A method as claimed in any preceding claim, wherein: Part A comprises an adhesion promoter in the form of a divalent metal salt of methacrylic acid, in particular zinc dimethacrylate.
14. A method as claimed in any preceding claim, wherein: Part A comprises the cross-linking agent.
15. As claimed in claim 14, wherein The cross-linking agent is a molecule having a molecular weight of 2,000 Da or less, preferably 1,000 Da or less, and two or more methacrylate groups.
16. As claimed in claim 14 or 15, wherein The cross-linking agent has a molecular weight of 900 Da or less.
17. As claimed in claim 14, 15 or 16, wherein The crosslinker has two methacrylate groups.
18. The method of claim 14, wherein the cross-linking agent has a molecular weight of 900 Da or less and two methacrylate groups.
19. A method as claimed in any preceding claim, wherein: Part A comprises a cross-linking agent having the following general formula II: wherein x and y are independently selected from 2-10, preferably, x and y are both 5.
20. A method as claimed in any preceding claim, wherein: Part A comprises, based on the total weight of part A, 0.5-2.5 wt %, more preferably 0.6-1.25 wt %, particularly preferably 0.6-0.8 wt % of a crosslinking agent.
21. A method as claimed in any preceding claim, wherein: Part A comprises a crosslinker having the general formula II and present in an amount of 0.5-2.5 wt %, based on the total weight of part A, more preferably 0.6-1.25 wt %, particularly preferably 0.6-0.8 wt %.
22. A method as claimed in any preceding claim, wherein: Part A comprises tetrahydrofurfuryl methacrylate, cyclohexyl methacrylate, and a divalent metal salt of methacrylic acid, particularly zinc dimethacrylate.
23. A method as claimed in any preceding claim, wherein: Based on the total weight of part A, the one or more methacrylate monomers other than the adhesion promoter and the crosslinking agent account for 10-30 wt % of part A, more preferably 12-25 wt %, particularly preferably 14-20 wt %.
24. A method as claimed in any preceding claim, wherein: Part A comprises 0.3-8 wt%, more preferably 0.5-5 wt%, of tetrahydrofurfuryl methacrylate based on the total weight of part A.
25. A method as claimed in any preceding claim, wherein: Part A comprises 5 to 20 wt %, more preferably 7 to 15 wt %, very particularly preferably 10 to 13 wt %, based on the total weight of part A, of cyclohexyl methacrylate.
26. A method as claimed in any preceding claim, wherein: Part A comprises 1-6 wt%, more preferably 2-4 wt%, of methacrylic acid based on the total weight of Part A.
27. A method as claimed in any preceding claim, wherein: Part A comprises 0.25-4 wt %, more preferably 0.5-1.5 wt %, of a divalent metal salt of methacrylic acid based on the total weight of Part A.
28. A method as claimed in any preceding claim, wherein: Part A comprises 0.5-4 wt %, more preferably 0.75-1.5 wt %, based on the total weight of Part A, of zinc dimethacrylate.
29. A method as claimed in any preceding claim, wherein: Part A comprises 0.3-8 wt%, more preferably 0.5-5 wt%, of tetrahydrofurfuryl methacrylate, based on the total weight of part A, and 5-20 wt%, more preferably 7-15 wt%, more particularly preferably 10-13 wt%, of cyclohexyl methacrylate, based on the total weight of part A.
30. A method as claimed in any preceding claim, wherein: Part A comprises 0.3-8 wt %, more preferably 0.5-5 wt %, of tetrahydrofurfuryl methacrylate, based on the total weight of part A, 5-20 wt %, more preferably 7-15 wt %, more particularly preferably 10-13 wt %, of cyclohexyl methacrylate, based on the total weight of part A, and 1-6 wt %, more preferably 2-4 wt %, of methacrylic acid, based on the total weight of part A.
31. A method as claimed in any preceding claim, wherein: Part A comprises 0.3-8 wt %, more preferably 0.5-5 wt %, of tetrahydrofurfuryl methacrylate, based on the total weight of part A, 5-20 wt %, more preferably 7-15 wt %, more particularly preferably 10-13 wt %, of cyclohexyl methacrylate, based on the total weight of part A, 1-6 wt %, more preferably 2-4 wt %, of methacrylic acid, based on the total weight of part A, and 0.5-4 wt %, more preferably 0.75-1.5 wt %, of zinc dimethacrylate, based on the total weight of part A.
32. A method as claimed in any preceding claim, wherein: The toughening agent is selected from the group consisting of polyether-based toughening agents and rubber-based toughening agents.
33. A method as claimed in any preceding claim, wherein: The toughening agent is a polyether based toughening agent prepared by reacting a polyether polyol with a polyisocyanate in a ratio such that the resulting polymer is an NCO terminated polymer, followed by end-capping with a hydroxyalkyl methacrylate.
34. A method as claimed in any preceding claim, wherein: The toughening agent is a rubber-based toughening agent, wherein the rubber is selected from polyurethane, silicone, polybutadiene, acrylonitrile butadiene, polyacrylate or polymethacrylate, and mixtures of these.
35. A method as claimed in any preceding claim, wherein: Part A comprises 5-20 wt %, more preferably 7-15 wt %, particularly preferably 8-12 wt %, of toughening agent (aii), based on the total weight of part A.
36. A method as claimed in any preceding claim, wherein: Part A comprises 5-20 wt%, more preferably 7-15 wt%, particularly preferably 8-12 wt% of a toughening agent (aii), based on the total weight of part A, wherein the toughening agent is a rubber-based toughening agent terminated with methacrylate groups.
37. Any preceding claim, wherein: Part A comprises 5-20 wt%, more preferably 7-15 wt%, particularly preferably 8-12 wt% of a toughener (aii), based on the total weight of part A, wherein the toughener is a rubber-based toughener terminated with methacrylate groups, wherein the rubber is selected from polyurethane, silicone, polybutadiene, acrylonitrile butadiene, polyacrylate or polymethacrylate, and mixtures of these.
38. A method as claimed in any preceding claim, wherein: Part A comprises 5-20 wt%, more preferably 7-15 wt%, particularly preferably 8-12 wt% of a toughener (aii), based on the total weight of part A, wherein the toughener is wherein the toughener is made by reacting an aliphatic polyether diol with an aliphatic diisocyanate and subsequently capping with a C2-C6-hydroxyalkyl ester, more preferably a C2-C4-hydroxyalkyl ester, even more preferably a C2-C3-hydroxyalkyl ester of methacrylate, wherein C2-hydroxyalkyl is most preferred (hydroxyethyl methacrylate, HEMA).
39. Any preceding claim, wherein: The phosphorus-containing compound (aiii) has formula IV, V and VI: wherein W are the same or different and each W is independently selected from H and a divalent organic group, wherein at least one W is a divalent organic group, and at least one X is vinyl, and the other X is vinyl or absent (in the case where W is H), or H.
40. Any preceding claim, wherein: The phosphorus-containing compound (aiii) has the formula VI.
41. Any preceding claim, wherein: The phosphorus-containing compound (aiii) has formula VI, and one, two or three X groups are vinyl groups; Preferably, one X group is vinyl.
42. Any preceding claim, wherein: The phosphorus-containing compound (aiii) has formula VI, and one, two or three WX groups have formula VII: The dot represents the point of attachment of the group, and in the case where one or two WX groups are of formula VII, the remaining WX groups are preferably H.
43. Any preceding claim, wherein: The phosphorus-containing compound (aiii) has the formula VIII:
44. Any preceding claim, wherein: The phosphorus-containing compound (aiii) has the formula IX:
45. Any preceding claim, wherein: The phosphorus-containing compound (aiii) is an approximately 2:1 mixture of Formula VIII and Formula IX.
46. Any preceding claim, wherein: The phosphorus-containing compound is selected from phosphoric acid; 2-methacryloyloxyethyl phosphate; bis-(2-methacryloyloxyethyl) phosphate; 2-acryloyloxyethyl phosphate; bis-(2-acryloyloxyethyl) phosphate; methyl-(2-methacryloyloxyethyl) phosphate; ethyl methacryloyloxyethyl phosphate; methacryloyloxyethyl phosphate; ethyl acryloyloxyethyl phosphate; propyl acryloyloxyethyl phosphate, isobutyl acryloyloxyethyl phosphate, ethylhexyl acryloyloxyethyl phosphate, halogenated propyl acryloyloxyethyl phosphate, halogenated isobutyl acryloyloxyethyl phosphate or halogenated ethylhexyl acryloyloxyethyl phosphate; Vinylphosphonic acid; cyclohexene-3-phosphonic acid; (α-hydroxybutylene-2-phosphonic acid; 1-hydroxy-1-phenylmethane-1,1-diphosphonic acid; 1-hydroxy-1-methyl-1-diphosphonic acid; 1-amino-1phenyl-1,1-diphosphonic acid; 3-amino-3-hydroxypropane-1,1-diphosphonic acid; amino-tri(methylenephosphonic acid); γ-amino-propylphosphonic acid; γ-glycidyloxypropylphosphonic acid; mono-2-aminoethyl phosphate; allylphosphonic acid; allylphosphinic acid; β-methacryloyloxyethylphosphinic acid; diallylphosphinic acid; β-methacryloyloxyethyl)phosphinic acid and allylmethacryloyloxyethylphosphinic acid.
47. Any preceding claim, wherein: The tertiary amine free radical initiator (aiv) has the general formula X: wherein W is selected from the group consisting of hydrogen, hydroxy, amino, halogen, alkyl having 1 to 8, preferably 1 to 4 carbon atoms, and alkoxy having 1 to 8, preferably 1 to 4 carbon atoms; R 1 and R 2 Independently selected from branched or straight chain C 1-4 -alkyl; and b is 1 or 2.
48. Any preceding claim, wherein: The tertiary amine free radical initiator is selected from N,N-dimethylaniline, N,N-dimethylaminomethylphenol and N,N-dimethyl-p-toluidine.
49. Any preceding claim, wherein: The tertiary amine free radical initiator is N,N-dimethyl-p-toluidine.
50. Any preceding claim, wherein: The tertiary amine free radical initiator is used in an amount of 0.1-0.6 wt % based on the total weight of Part A, more preferably 0.2-0.4 wt %.
51. Any preceding claim, wherein: The tertiary amine free radical initiator is N,N-dimethyl-p-toluidine, which is used at 0.1-0.6 wt %, more preferably 0.2-0.4 wt %, based on the total weight of Part A.
52. Any preceding claim, wherein: Diethylhydroxylamine is present in Part A at 0.015-0.06 wt %, based on the total weight of Part A, more preferably 0.2-0.055 wt %.
53. Any preceding claim, wherein: The at least one epoxy resin comprises the reaction product of epichlorohydrin and bisphenol-A.
54. Any preceding claim, wherein: The at least one epoxy resin comprises an epoxy resin that is a liquid reaction product of epichlorohydrin and bisphenol A, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
55. Any preceding claim, wherein: The at least one epoxy resin comprises a bisphenol A / F-based epoxy resin having an epoxy equivalent weight of 345-365 g / equivalent.
56. Any preceding claim, wherein: The at least one epoxy resin comprises a mixture of a liquid reaction product of epichlorohydrin and bisphenol A and an epoxy resin based on bisphenol A / F with an epoxy equivalent weight of 345-365 g / equivalent, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
57. Any preceding claim, wherein: The at least one epoxy resin comprises 50-95 wt%, more preferably 60-80 wt%, based on the total weight of the epoxy resins in part B, of a liquid reaction product of epichlorohydrin and bisphenol A, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
58. Any preceding claim, wherein: The at least one epoxy resin comprises 5-50 wt%, more preferably 20-40 wt%, based on the total weight of the epoxy resins in Part B, of a bisphenol A / F based epoxy resin having an epoxy equivalent weight of 345-365 g / equivalent.
59. Any preceding claim, wherein: The at least one epoxy resin comprises, based on the total weight of the epoxy resins in part B, 50-95 wt%, more preferably 60-80 wt%, of a liquid reaction product of epichlorohydrin and bisphenol A and 5-50 wt%, more preferably 20-40 wt%, of an epoxy resin based on bisphenol A / F with an epoxy equivalent weight of 345-365 g / equivalent, the liquid reaction product having an epoxy equivalent weight of 182-192 g / equivalent (as measured according to ASTM D-1652), an epoxy percentage of 22.4%-23.6% (as measured according to ASTM D-1652), an epoxy group content of 5,200-5,500 mmol / kg (as measured according to ASTM D-1652), and a viscosity of 11,000-14,000 mPas at 25° C. (as measured according to ASTM D-445).
60. Any preceding claim, wherein: Part B comprises, based on the total weight of part B, 10 to 30 wt %, more preferably 12 to 20 wt %, very particularly preferably 14 to 16 wt % of the at least one epoxy resin.
61. Any preceding claim, wherein: The oxidizing agent (bi) is selected from organic peroxides.
62. Any preceding claim, wherein: The oxidizing agent (bi) is selected from the group consisting of diacyl peroxides, hydroperoxides, peresters, and ketone hydroperoxides.
63. Any preceding claim, wherein: The oxidizing agent (bi) is selected from benzoyl peroxide, cumene hydroperoxide, β-butyl peroxybenzoate, and methyl ethyl ketone hydroperoxide.
64. Any preceding claim, wherein: The oxidizing agent (bi) is benzoyl peroxide.
65. Any preceding claim, wherein: The oxidizing agent (bi) is present in part B at 1.5-5 wt% based on the total weight of part B, more preferably 2-4 wt%.
66. Any preceding claim, wherein: Part B comprises 1.5-5 wt%, more preferably 2-4 wt%, of benzoyl peroxide based on the total weight of Part B.
67. Any preceding claim, wherein: The thermally conductive filler comprises, consists essentially of, or consists entirely of one or more thermally conductive fillers having a thermal conductivity of about 3 W / mK to about 80 W / mK.
68. Any preceding claim, wherein: The thermally conductive filler is selected from aluminum hydroxide, aluminum oxide, aluminum powder, zinc oxide, boron nitride, and mixtures thereof.
69. Any preceding claim, wherein: The thermally conductive filler is aluminum hydroxide.
70. Any preceding claim, wherein: The adhesive mixture formed by combining Part A and Part B contains sufficient thermally conductive filler such that the thermal conductivity of the adhesive mixture after curing is at least about 0.9 W / mK or greater, preferably about 1.0 W / mK or greater.
71. Any preceding claim, wherein: The thermally conductive filler is ATH having a multimodal particle size distribution.
72. Any preceding claim, wherein: The thermally conductive filler is ATH having a bimodal particle size distribution.
73. Any preceding claim, wherein: The thermally conductive filler is alumina trihydrate having the following particle size distribution: D 10 =0.5μm D 50 =8μm D 90 =80μm。 74. Any preceding claim, wherein: The thermally conductive filler is present in part A and / or part B such that when the two components are mixed (preferably in a volume ratio of 2:1 to 10:1, more preferably 4:1) to form an adhesive mixture, the concentration of the thermally conductive filler in the adhesive mixture is at least 40 wt% based on the total weight of the adhesive mixture.
75. Any preceding claim, wherein: The thermally conductive filler is present in part A and / or part B such that when the two components are mixed (preferably in a volume ratio of 2:1 to 10:1, more preferably 4:1) to form an adhesive mixture, the concentration of the thermally conductive filler in the adhesive mixture is 55-65 wt% based on the total weight of the adhesive mixture.
76. Any preceding claim, wherein: The thermally conductive filler is present in Part A, Part B, or both.
77. Any preceding claim, wherein: Both part A and part B contain thermally conductive fillers.
78. Any preceding claim, wherein: The concentration of the thermally conductive filler in part A is 40-90 wt %, more preferably 55-62 wt %, particularly preferably 44-57 wt %, based on the total weight of part A.
79. Any preceding claim, wherein: The concentration of the thermally conductive filler in part B is 55-90 wt %, based on the total weight of part B, more preferably 60-70 wt %, particularly preferably 44-57 wt %.
80. Any preceding claim, wherein: The concentration of the thermally conductive filler in part A is 40-90 wt%, more preferably 55-62 wt%, and particularly preferably 44-57 wt%, based on the total weight of part A, and the concentration of the thermally conductive filler in part B is 55-90 wt%, more preferably 60-70 wt%, and particularly preferably 44-57 wt%, based on the total weight of part B.
81. Any preceding claim, wherein: The adhesives of the present invention show lap shear strength of 10 MPa or greater on cold rolled steel using the following test method: Specimens were prepared and tested according to SAE J1523 [2012 02 01], 25.4 mm x 101.6 mm specimens were mated at 12.7 mm overlap and 0.10 mm bond line thickness, and then allowed to cure at room temperature, the specimens were tested at a rate of 12.7 mm / min.
82. Any preceding claim, wherein: The adhesive of the present invention shows a lap shear strength of 10 MPa or greater on nickel-plated steel using the following test method: Specimens were prepared and tested according to SAE J1523 [2012 02 01], 25.4 mm x 101.6 mm specimens were mated at 12.7 mm overlap and 0.10 mm bond line thickness, and then allowed to cure at room temperature, the specimens were tested at a rate of 12.7 mm / min.
83. Any preceding claim, wherein: When tested for lap shear strength as described above, the adhesives of the present invention exhibit a failure mode of at least 90%, more preferably at least 95%, cohesive failure on cold rolled steel.
84. Any preceding claim, wherein: When tested for lap shear strength as described above, the adhesives of the present invention exhibit a failure mode of at least 50%, more preferably at least 80% cohesive failure on nickel plated steel.
85. Any preceding claim, wherein: The adhesive of the present invention showed good storage stability as evidenced by the lack of gelation of Part A after heat aging at 54°C for two weeks.